Eficacia de las tiras reactivas de uroanálisis en el diagnóstico de infección del tracto urinario - Changllio Roas, Juan José E. (2023)
To evaluate the efficacy of uroanalysis test strips in the rapid diagnosis of urinary tract infection in women. Material and Methods: Observational, analytical, cross-sectional, and prospective study. The unit of analysis was women with urinary tract infection attending the Tirapata Health Establishment, Province of Azángaro, Department of Puno. Urine samples were requested, and sediment was analyzed using reagent strips. Data were obtained by epidemiological analysis of tabulated data for diagnostic tests of sensitivity and specificity. Results: 114 cases were confirmed with UTI (95 %). The pH obtained was acidic in 84,2 % and basic in 15,8 % of the samples with PPV 78,95% and NPV 1,98 %. The results showed 26,7 % of nitrites with PPV 93,75 % and NPV 4,55 %; 93,3 % of leukocytes with PPV 99,11 % and NPV 62,5 % and 58,3 % presence of blood with PPV 94,29% and NPV 4 %. Presenting high efficacy, showing sensitivity of 97,37 % and specificity of 83,33 %. Conclusion: The efficacy of the test strips is high with a sensitivity of 97,37 % and specificity of 83,33 %.